ANALISIS WEWENANG PENYIDIK DALAM PENYIDIKAN KASUS TINDAK PIDANA PENGEROYOKAN DI SATRESKRIM POLRES KERINCI: ELIYUSNADI, S.Kom., M.Si - Eliyusnadi (LPPM STIA Nusantara Sakti, 2018)
The research in this thesis aims to find out the authority of investigators in the investigation of beatings in the Kerinci Criminal Investigation Unit. This research was conducted in the Kerinci Police Precinct Criminal Investigation Section, the research method used was juridical empirical by using data collection techniques through field studies namely conducting direct interviews with investigators / auxiliary investigators of Kerinci Polres Satreskrim as well as interviews with victims and suspects of beating crimes, determination of iformans in research This uses a purposive technique and literature study by reading documents relating to the problem under study to look for concepts, theories, opinions or findings related to the subject matter. Based on the results of the study, conclusions are obtained, reports / complaints in this case the report must be studied first and then followed up. Second, secure the suspect, secure evidence. Third, check the identity, do not make mistakes, the wrong catch, wrong arrest can harm someone who does not know anything. All four arrests must have evidence or other conditions that support the arrest can be made. The five fingerprints need to be done especially on victims who have died if the victim's identity is unknown, on the evidence can also be fingerprinted to find out the identity of the perpetrator. The sixth summoned witnesses or suspects for questioning. Investigators gave summons, but if they were not met three times, the investigator could summon by force. Seventh termination of an investigation can be carried out if there is not enough evidence but if later evidence is found, the investigation can continue.